2015
DOI: 10.4102/curationis.v38i1.1266
|View full text |Cite
|
Sign up to set email alerts
|

Why do women not return for CD4 count results at Embhuleni Hospital, Mpumalanga, South Africa?

Abstract: BackgroundAccording to the South African Policy and guidelines for the implementation of the PMTCT programme of 2008, all pregnant women who tested HIV-positive also had to have their CD4 count measured in order to inform the option of Prevention of Mother-to-Child Treatment (PMTCT): to be put on lifelong treatment or to be placed on temporary PMTCT. They were required to return for the results within two weeks, but some did not return, implying that they did not benefit from the programme. This study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…We observed that involuntary HIV status disclosure related to participation in HIV care was the most common social concern among pregnant women in our study. In line with our results, previous qualitative studies from SSA and Asia have reported that concern about unintentional HIV status disclosure has been identified as a barrier to visiting PMTCT care facilities [13][14][15][16][17][18]. Concern about involuntary HIV disclosure has been suggested to limit access to care by promoting fear and isolation among pregnant women in Kenya [13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed that involuntary HIV status disclosure related to participation in HIV care was the most common social concern among pregnant women in our study. In line with our results, previous qualitative studies from SSA and Asia have reported that concern about unintentional HIV status disclosure has been identified as a barrier to visiting PMTCT care facilities [13][14][15][16][17][18]. Concern about involuntary HIV disclosure has been suggested to limit access to care by promoting fear and isolation among pregnant women in Kenya [13].…”
Section: Discussionsupporting
confidence: 88%
“…PMTCT care as well as ART to prevent sexual transmission, condom use, and voluntary male medical circumcision are successful strategies for HIV prevention in low and middle-income countries [2,3,12]. However, qualitative evidence from sub-Saharan Africa (SSA) and Asia has shown that concerns about unintentional HIV status disclosure and HIV related stigma are barriers to participate in PMTCT care among pregnant women [13][14][15][16][17][18]. Qualitative studies have also identified other important barriers to HIV status disclosure including concerns about separation or divorce [19][20][21][22][23], conflicts with a partner [19,21], intimate partner violence (IPV) [19][20][21]23] and stigma in the family or community [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…Fear of unintended HIV status disclosure and its repercussion when attending clinic appointments deters health‐seeking behaviour. Often people living with HIV fear attending local community healthcare facilities and will sometimes choose to attend clinics that are far from their local facilities to avoid being recognized 53,54 . Also, harsh treatment from clinic staff and stigmatizing language often lead to a feeling of moral failing and shame, resulting in treatment interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Often people living with HIV fear attending local community healthcare facilities and will sometimes choose to attend clinics that are far from their local facilities to avoid being recognized. 53 , 54 Also, harsh treatment from clinic staff and stigmatizing language often lead to a feeling of moral failing and shame, resulting in treatment interruption. Incorporating facility‐wide stigma‐reduction strategies in staff training and health programmes would foster improved patient–clinic staff relationships.…”
Section: Discussionmentioning
confidence: 99%